MODE OF ARGUMENTATION IN NATIONAL UNIVERSITY DEBATE CHAMPIONSHIP (NUDC) 2021 - Zeli Wahyu sang Putri; Ririn Putri Ananda (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Debate is an activity to fight for the team's argument by presenting strong and relevant evidence so that the team's argument wins, convincing the jury that the team's argument is valid, strong, and true. Therefore, debate participants need to know the mode of their argument. The purpose of this study is to identify and describe the dominant mode of argumentation used by debaters at the 2021 National University Debating Championship (NUDC). The research design of this study used a qualitative descriptive method. The instrument used is an observation sheet. The subjects of this study were the participants of the Open Quarterfinals room D1 (NUDC) 2021, Open Semifinals D1 (NUDC) 2021, and Novice Grandfinals (NUDC) 2021 debates. The results of this study indicate that the debate participants used all the argumentation modes in NUDC and the most used or the most dominant argumentation mode was evaluative argumentation. For future researchers, it is recommended to conduct an in-depth investigation of the debate. Keywords: Speaking, Debate, Mode, Argumentation